2014
DOI: 10.1371/journal.pone.0103419
|View full text |Cite
|
Sign up to set email alerts
|

Molluscum Contagiosum in a Pediatric American Indian Population: Incidence and Risk Factors

Abstract: BackgroundMolluscum contagiosum virus (MCV) causes an innocuous yet persistent skin infection in immunocompetent individuals and is spread by contact with lesions. Studies point to atopic dermatitis (AD) as a risk factor for MCV infection; however, there are no longitudinal studies that have evaluated this hypothesis.MethodsOutpatient visit data from fiscal years 2001–2009 for American Indian and Alaska Native (AI/AN) children were examined to describe the incidence of molluscum contagiosum (MC). We conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 24 publications
(33 reference statements)
1
12
0
2
Order By: Relevance
“…A case-control study of children aged ≤5 years identified following outpatient visits in the US found that those with a diagnosis of MC were more likely to have either a current or previous AE diagnosis than controls. 15 Another case-control study identified children with MC and compared the prevalence of AE with that of a previous national cross-sectional study. It found a prevalence of 18.2% in the MC cohort and 5% in the national survey.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…A case-control study of children aged ≤5 years identified following outpatient visits in the US found that those with a diagnosis of MC were more likely to have either a current or previous AE diagnosis than controls. 15 Another case-control study identified children with MC and compared the prevalence of AE with that of a previous national cross-sectional study. It found a prevalence of 18.2% in the MC cohort and 5% in the national survey.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…8 Atopic eczema (AE) has been found to be common in children with MC, [9][10][11][12][13] and the prevalence of AE is higher in children with MC than in the general population. 14,15 However, most studies describing this association have been based in specialty dermatology clinics, 12 and have not explored the temporal relationship between the two conditions. It is not clear whether this relationship holds for children with AE or MC in the community, or whether there is a time-dependent direction, in other words, that children with AE are more likely to develop MC.…”
Section: Introductionmentioning
confidence: 99%
“…Most previous research has also demonstrated an association between AE and MC. A case-control study of children aged 5 years and under identified following outpatient visits in North America found that those with a diagnosis of MC were more likely to have a either a current or previous AE diagnosis when compared to controls (15). Another casecontrol study identified children with MC and compared the prevalence of AE with that of a previous national cross-sectional study.…”
Section: Comparison With Existing Literaturementioning
confidence: 99%
“…Atopic eczema (AE) has been found to be common in children with MC (9-13) and the prevalence of AE is higher in children with MC than in the general population (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…Molluscum contagiosum (MC) is a common skin infection caused by a poxvirus and generally observed in children. MC lesions typically appear as single or multiple, small (2–5 mm), flesh‐coloured and translucent papules with a characteristic central umbilication …”
Section: Introductionmentioning
confidence: 99%